PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL TPS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII MTs MUHAMMADIYAH 02 PEKANBARU - Siska Endah Sari; Zuhri D '; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research aims to determine the influence of the implementation of problem solving strategy in TPS structural approach of cooperatif learning to the mathematical problem solving ability of students. This research was conducted in MTs Muhammadiyah 02 Pekanbaru on odd semester academic year 2016/2017. This is a pre-experimental research which using the Static-Group Comparison design. The population is all of students at grade VIII in MTs Muhammadiyah 02 Pekanbaru. Samlples in the research involved two groups were selected by purposive sampling technic. Class VIII4 consisting 25 students as experimental class was implemented the problem solving strategy in TPS structural approach of cooperative learning and class VIII1 consisting 28 students as control class was implemented TPS structural approach of cooperative learning. The instrument of collecting data in this research is initial ability test and mathematical problem solving ability test. This research shows that average value of mathematical problem solving ability in the experimental class is better than the control class. It can be conclude that the application of ptoblem solving strategy in TPS structural approach of cooperatif learning positively affect the mathematical problem solving ability of students of class VIII MTs Muhammadiyah 02 Pekanbaru.